MAZ51 Blocks the Tumor Growth of Prostate Cancer by Inhibiting Vascular Endothelial Growth Factor Receptor 3 - Yamamura, Aya; Nayeem, Md Junayed; Muramatsu, Hiroyuki; Nakamura, Kogenta; Sato, Motohiko (Frontiers in Pharmacology, 2021)
Vascular endothelial growth factor (VEGF) signaling plays a critical role in the carcinogenesis and tumor development of several cancer types. However, its pathological significance in prostate cancer, one of the most frequent and lethal malignancies in men, remains unclear. In the present study, we focused on a pathological role of the VEGF receptors (VEGFRs), and examined their expression and effects of MAZ51 (an inhibitor of the tyrosine kinase of VEGFR-3) on cell proliferation, migration, and tumor growth in human prostate cancer cells. The expression level of VEGFR-3 was higher in androgen-independent and highly metastatic prostate cancer PC-3 cells than in other prostate PrEC, LNCaP, and DU145 cells. In PC-3 cells, VEGFR-3 and Akt were phosphorylated following a stimulation with 50 ng/ml VEGF-C, and these phosphorylations were blocked by 3 uM MAZ51. Interestingly, PC-3 cells themselves secreted VEGF-C, which was markedly larger amount compared with PrEC, LNCaP, and DU145 cells. The expression of VEGFR-3 was reduced by MAZ51. The proliferation of PC-3 cells was inhibited by MAZ51 (IC50 = 2.7 uM) and partly decreased by 100 nM GSK690693 (an Akt inhibitor) and 300 nM VEGFR2 Kinase Inhibitor I. MAZ51 also attenuated the VEGF-C-induced migration of PC-3 cells. Moreover, MAZ51 blocked the tumor growth of PC-3 cells in a xenograft mouse model. These results suggest that VEGFR-3 signaling contributes to the cell proliferation, migration, and tumor growth of androgen-independent/highly metastatic prostate cancer. Therefore, the inhibition of VEGFR-3 has potential as a novel therapeutic target for the treatment for prostate cancer.